Structural Convergence of European Economies – Literature Review - Damyanov, Dimitar (Research Papers, 2020)
Structural convergence in the EU is regarded as an important prerequisite for the efficient functioning of the Economic and monetary union. This article presents a brief review of the existing theoretical and empirical literature regarding the convergence of output structures among countries. The analysis of the theoretical literature identifies a wide variety of factors driving the process. In line with that, conflicting evidence about the EU’s past experience with convergence can be found in empirical studies.
Keywords: Economic integration; Structural change; Monetary unions; Structural convergence